Gestión de las obligaciones tributarias a la empresa Jehová Shalon de la Parroquia San Juan - Contreras Chacha, Jhon Henrry (2021)
Tax Management is the set of actions aimed at designing tax and tax incentives for companies and low-income taxpayers, allowing to achieve economic advantages, it must adopt accounting records of invoicing and adequate vouchers to validate the presentation of the statements with quality and efficiency. financial, these situations tend to cause prejudice to the company because it does not know what the real values of its finances are, how much are its real expenses and income and its annual profit. This case study provides important information regarding the Management of Tax Obligations to the Jehovah Shalon Company of the San Juan parish, Cantón Pueblo Viejo, Los Ríos province, the same as supported by the Organic Law of Internal Tax Regime and its Regulations. Ecuadorian, and Tax Code that govern the institutions. The technique used to obtain data and information on the respective case study was the interview, a direct approach made to the owner of the company, and through an inspection of their accounting records such as sales and invoicing receipts, findings were found. important that are related in the development of the case. This case study was designed with the purpose of contributing knowledge about the results of the management of tax obligations, framed by the Financial, Tax and Social Commitment Management model as a line of research.